2009
DOI: 10.1097/prs.0b013e3181904d86
|View full text |Cite
|
Sign up to set email alerts
|

Marjolin's Ulcer: Modern Analysis of an Ancient Problem

Abstract: The authors' review suggests that there is much variability in the anatomical location of Marjolin's ulcers, with the majority occurring in wounds of the upper and lower extremities. Marjolin's ulcer appears to be preventable if early wound coverage is undertaken. Countries with limited access to medical treatment report a high number of Marjolin's ulcers compared with more developed regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
117
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(139 citation statements)
references
References 22 publications
5
117
0
8
Order By: Relevance
“…The most common inciting injury in various studies has been the thermal injury and it stands true in our study as well [2]. Although no age is immune to development of MU, it has been reported that the latency period between the initial insult and development of MU is inversely proportional to the age at initial insult [8].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The most common inciting injury in various studies has been the thermal injury and it stands true in our study as well [2]. Although no age is immune to development of MU, it has been reported that the latency period between the initial insult and development of MU is inversely proportional to the age at initial insult [8].…”
Section: Discussionmentioning
confidence: 54%
“…Both these characters were later identified by Robert William Smith but it was not until 1903 when JC Dacosta described these ulcers and coined the term "Marjolin's Ulcer" that this was established as a distinct pathology [1]. Although MU can arise from any chronic wound or non-healing scar, neglected burn scars are the commonest site of its origin [2]. This entity is thought to be rare in developed countries but it is common in developing countries because of a higher incidence of thermal injuries due to use of coal, cow dung cakes, wood and kerosene oil as fuel for cooking.…”
Section: Introductionmentioning
confidence: 99%
“…2 Marjolin's ulcer may develop in various anatomical locations, although the highest incidence is in the lower extremities. 1,5 The predilection of these lesions may be due to injuries that affect the arms and legs, such as a grenade shrapnel injury in this case. The transformation from ulcer to malignancy is typically slow and the pathogenesis is unclear, 5,6 but it is most likely multifactorial.…”
Section: Discussionmentioning
confidence: 92%
“…1,5 The predilection of these lesions may be due to injuries that affect the arms and legs, such as a grenade shrapnel injury in this case. The transformation from ulcer to malignancy is typically slow and the pathogenesis is unclear, 5,6 but it is most likely multifactorial. 7 Chronic foreign body induced inflammation from retained shrapnel fragments appears to be the cause in our patient's case.…”
Section: Discussionmentioning
confidence: 92%
“…The transition time is variable, ranging from three months to 63 years. The average transition time is 26 years [3]. Over the years the transition time is getting shorter.…”
Section: Editorialmentioning
confidence: 95%